2018
DOI: 10.1021/acs.jced.8b00188
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Salt Type and Alkyl Chain Length on the Binodal Curve of an Aqueous Two-Phase System Composed of Imidazolium Ionic Liquids

Abstract: The binodal data for an aqueous two-phase system (ATPS) containing 1-alkyl-3-methylimidazolium tetrafluoroborate ([C n mim]­BF4, n = 2, 3, 4) or 1-alkyl-3-methylimidazolium chloride ([C n mim]­Cl], n = 2, 4, 6, 8, 10, 12) and inorganic salts (K2HPO4, NaH2PO4, (NH4)2SO4, and NaCl) or organic salts (sodium citrate, sodium tartrate, and sodium acetate) were widely determined at T = 298.15 K. The various binodal curves could be fitted and summarized as two kinds of empirical nonlinear equations with the lowest sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 52 publications
2
6
0
Order By: Relevance
“…The literature report which published the [C 4 C 1 im]Br + Na 3 C 6 H 5 O 7 + water system found that lower temperatures are favorable for the formation of IL-ABS, whereas there are also some phase diagrams which were not affected apparently by the temperature . Another important aspect is the research studies concerning the influence of various salts on phase diagrams. , For example, the effect of salts on ABSs was evaluated by Mara and his group. , It was demonstrated that the additive salt only slightly affected the phase equilibrium of two-phase aqueous solutions, and the ILs play a more important role in causing the phase separation . Therefore, appropriate cations and anions of the ILs can be chosen to study the reason for the various abilities of different systems to form ABSs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature report which published the [C 4 C 1 im]Br + Na 3 C 6 H 5 O 7 + water system found that lower temperatures are favorable for the formation of IL-ABS, whereas there are also some phase diagrams which were not affected apparently by the temperature . Another important aspect is the research studies concerning the influence of various salts on phase diagrams. , For example, the effect of salts on ABSs was evaluated by Mara and his group. , It was demonstrated that the additive salt only slightly affected the phase equilibrium of two-phase aqueous solutions, and the ILs play a more important role in causing the phase separation . Therefore, appropriate cations and anions of the ILs can be chosen to study the reason for the various abilities of different systems to form ABSs.…”
Section: Introductionmentioning
confidence: 99%
“…17,18 For example, the effect of salts on ABSs was evaluated by Mara and his group. 19,20 It was demonstrated that the additive salt only slightly affected the phase equilibrium of two-phase aqueous solutions, and the ILs play a more important role in causing the phase separation. 21 anions of the ILs can be chosen to study the reason for the various abilities of different systems to form ABSs.…”
Section: Introductionmentioning
confidence: 99%
“…ATPS has some advantages, such as short processing time, gentle biocompatible environment, and no use of toxic volatile organic solvent in the experiment. Usual types of ATPS include two different polymers ATPS, polymer‐salt ATPS, ionic liquid (IL)‐salt ATPS, and small molecular water‐miscible organic solvent‐salt ATPS . The application of polymer‐polymer and polymer‐salt ATPS has been restricted as their shortcomings such as high viscosity, difficulty in phase separation, and easily emulsify.…”
Section: Introductionmentioning
confidence: 99%
“…Ionic liquid aqueous two-phase systems (ILATPS), which were first proposed by Gutowski in 2003, are usually formed by ionic liquid + salt + water and combine the advantages of ionic liquids and ATPS . So far, a number of IL and salt ATPS have been reported. ILATPS have been extensively used to extract protein, phenolic compound, polysaccharides, and chloramphenicol . The liquid–liquid equilibrium data of these ILATPS are significant to these extractions .…”
Section: Introductionmentioning
confidence: 99%